PENGARUH EXPERIENTIAL MARKETING TERHADAP MINAT BERKUNJUNG ULANG DENGAN KEPUASAN PENGUNJUNG SEBAGAI VARIABEL MEDIASI (Survei pada Pengunjung Taman Pelangi Jurug Surakarta) - Tastri, Yeni Yulfi; Rahadhini, Marjam Desma; Triastity, Rahayu (Universitas Slamet Riyadi, 2019)
The purpose of this study is to analyze the significance effect of experiential marketing on visitor satisfaction, analyze the significance effect of visitor satisfaction on intention to revisit, analyze the significance of experiential marketing on intention to revisit, and analyze the visitor satisfaction mediates effect of experiential marketing on intention to revisit. The data used are quantitative and qualitative data. Data sources use primary and secondary data. The population in study were all unknown numbers of visitors to the Taman Pelangi. The sampling technique using the accidental sampling technique was 100 respondents. Data collection techniques with questionnaires, literature studies, and observatios. Data analysis techniques used are classic assumption test, descriptive analysis, t tes, f test, coefficient of determination, and sobel test. The results of the study indicate that experiential marketing has an effect on visitor satisfaction, visitor satisfaction has an effect on intention to revisit, experiential marketing has an effect on revisit to intention, visitor satisfaction mediated effect of experiential marketing on intention to revisit.